STRATEGI KOMUNITAS PEDAGANG MUSLIM APEM DALAM MENJAGA STABILITAS PENDAPATAN DI DESA KESESI - Putri Artika Fitriani (J-MD Jurnal Manajemen Dakwah, 2023)
The Covid-19 pandemic has become a global problem that has had an impact on various sectors, especially the economic sector. Indonesia itself experienced a drastic economic decline of 2.07 percent according to the Central Statistics Agency (BPS). For two years Indonesia has experienced the Covid-19 pandemic. Not yet fully resolve other problems that arise, namely the problem of war that occurred between Ukraine and Russia. This resulted in the world food sector experiencing a crisis. Indirectly, this vulnerability has an impact on the trade sector, but through a SWOT analysis this does not have a major impact on apem traders in the Kesesi area. Because apem traders in the Kesesi area have a strategy to maintain the quality of their products so that income stability is maintained. The method used in this research is qualitative research because the writer collected the data by observing directly at Kesesi Village through interviews with several apem traders in Kesesi Village. The results of this study are the strategies used by apem traders in maintaining the stability of their income by maintaining the quality of the apem products.